4E-BP1 expression in embryonic postmitotic neurons mitigates mTORC1-induced cortical malformations and behavioral seizure severity but does not prevent epilepsy in mice - Nguyen, Lena H.; Sharma, Manas; Bordey, Angelique (Frontiers in Neuroscience, 2023)
Hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) pathway during neurodevelopment leads to focal cortical malformations associated with intractable seizures. Recent evidence suggests that dysregulated cap-dependent translation downstream of mTORC1 contributes to cytoarchitectural abnormalities and seizure activity. Here, we examined whether reducing cap-dependent translation by expressing a constitutively active form of the translational repressor, 4E-BP1, downstream of mTORC1 would prevent the development of cortical malformations and seizures. 4E-BP1CA was expressed embryonically either in radial glia (neural progenitor cells) that generate cortical layer 2/3 pyramidal neurons or in migrating neurons destined to layer 2/3 using a conditional expression system. In both conditions, 4E-BP1CA expression reduced mTORC1-induced neuronal hypertrophy and alleviated cortical mislamination, but a subset of ectopic neurons persisted in the deep layers and the white matter. Despite the above improvements, 4E-BP1CA expression in radial glia had no effects on seizure frequency and further exacerbated behavioral seizure severity associated with mTORC1 hyperactivation. In contrast, conditional 4E-BP1CA expression in migratory neurons mitigated the severity of behavioral seizures but the seizure frequency remained unchanged. These findings advise against targeting 4E-BPs by 4E-BP1CA expression during embryonic development for seizure prevention and suggest the presence of a development-dependent role for 4E-BPs in mTORC1-induced epilepsy.